Bahasa Inggris Analysis of Mathematical Literacy Ability of Grade XI Senior High School Students - Ahmad Lutfi Fauzi; Elah Nurlaelah (Universitas Sarjanawiyata Tamansiswa, 2023)
Mathematical literacy skills are important in the 21st century. Mathematical literacy skills are an indicator of being able to solve a problem in text or everyday life. This study aims to describe and illustrate the mathematical literacy skills in one of the high schools in Bandung based on mathematical ability and AKM. The researcher uses a qualitative descriptive research type. The instruments used are in the form of tests and interviews. The subjects of this research are students of class XI SMA in Bandung. Data obtained by giving students questions about mathematical literacy skills with trigonometric material. The results of the study show that there are three groupings for mathematical literacy ability, low, medium and high mathematical literacy ability. The results of this study almost all students belong to the high group, with a percentage of 50%, 36% including the medium group and 14% in the low category.